Junior High School Students' Anxiety in English Essay Writing - Bertha Pasaribu; Wisma Yunita (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Writing anxiety is a prevalent issue encounter by junior high school students, particularly when tasked with writing English essay. This study investigated anxiety factors faced by junior high school students in writing English essays. The research aims to identify the level and the types of anxiety faced by junior high school writing English essay. The study used mixed method. The data collected through questionnaires. The study's population 45 students at SMPN 29 Bengkulu Tengah. A close-ended questionnaire, adapted from the Second Language Writing Anxiety Inventory (SLWAI) by Cheng (2004), and interview that used to assess levels of somatic, cognitive, and avoidance anxiety. This study revealed that majority of students felt high-anxiety (84.44%) in writing English essay. This study also discovered that, with a mean score of 30.67, cognitive anxiety is the most prevalent type of writing anxiety.